Newly established bermudagrass response to topramezone and photosystem II-inhibitor herbicides - Raphael M. Negrisoli; D. Calvin Odero (Weed Technology, 2025)
Bermudagrass is the most troublesome and difficult-to-control perennial grass weed in Florida sugarcane. Once established, it may be effectively controlled only during the sugarcane fallow period using a combination of nonselective herbicides and tillage. Options for selective management of bermudagrass that escape sugarcane fallow period management programs must be evaluated to mitigate its progressive increase as the crop cycle increases from plant cane to ratoon crops. Greenhouse and field studies were conducted in Belle Glade, Florida, from 2017 to 2018, to determine the response of newly established bermudagrass from sprigs with stolons to two or three sequential applications of topramezone (25 and 50 g ha−1) every 14 d, and combinations of topramezone (25 and 50 g ha−1) with herbicides that inhibit photosystem II (PS II) such as atrazine (2,240 g ha−1), ametryn (440 g ha−1), and metribuzin (2,240 g ha−1). Two or three sequential applications of topramezone with a cumulative total of 75 to 100 g ha−1 provided >93% bermudagrass control 42 d after the first sequential application under greenhouse and field conditions. These treatments exhibited 12% chance of survival 70 d after the first sequential application. There was an additive effect of PS II-inhibitor herbicides on bermudagrass control in mixtures with topramezone. The mixture of topramezone (50 g ha−1) with metribuzin and atrazine provided more than 87% and 92% bermudagrass control under greenhouse and field conditions, respectively, 42 d after treatment. Bermudagrass treated with topramezone (50 g ha−1) in a mixture with metribuzin exhibited 23% chance of survival 70 d after treatment. The results show good efficacy of sequential topramezone applications every 14 d or in a mixture with the PS II-inhibitor herbicides atrazine and metribuzin for control of newly established bermudagrass that typically escape control measures during the sugarcane fallow management period.